Pengaruh Likuiditas, Solvabilitas, dan Profitabilitas Terhadap Return Saham pada Perusahaan Manufaktur Sektor Makanan dan Minuman - Yusmeco, Vito Alviandri; Hermuningsih, Sri; Kusumawardhani, Ratih (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study aims to examine and analyze the effect of liquidity, solvency and profitability on stock returns in Manufacturing companies in the Food and Beverage sector listed on the Indonesia Stock Exchange in 2017-2021. The population in this study were 21 companies in the Food and Beverage sector. The technique used in sampling in this study was purposive sampling, and a total sample of 12 companies was obtained. The analytical method used in this study is a quantitative analysis method using Microsoft Excel 2010 as a data tabulation tool and Statistical Product and Service Solutions (SPSS) version 21 as a tool used to test research data. The data used in this study is secondary data taken from the annual financial reports of Manufacturing companies in the Food and Beverage sector listed on the Indonesia Stock Exchange (IDX) during the 2017-2021 research period which can be accessed through the official website, namely www.idx.co. id, and other journals or articles related to this research. The results of this study indicate that liquidity as measured by CR has a negative and insignificant effect on stock returns, solvability as measured by (DER) has a negative and insignificant effect on stock returns, and profitability as measured by (ROA) has a positive and significant effect on returns. share.